2016
DOI: 10.1016/j.celrep.2016.08.078
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Regulates Proliferation and Neurogenic Potential of Müller Glial Cells via a Lin28/let-7 miRNA-Dependent Pathway in Adult Mammalian Retinas

Abstract: In cold-blooded vertebrates such as zebrafish, Müller glial cells (MGs) readily proliferate to replenish lost retinal neurons. In mammals, however, MGs lack regenerative capability as they do not spontaneously re-enter the cell cycle unless the retina is injured. Here, we show that gene transfer of β-catenin in adult mouse retina activates Wnt signaling and MG proliferation without retinal injury. Upstream of Wnt, deletion of GSK3β stabilizes β-catenin and activates MG proliferation. Downstream of Wnt, β-caten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
166
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(177 citation statements)
references
References 61 publications
10
166
1
Order By: Relevance
“…There is evidence for cross-talk between many of these pathways with NF-ĸB signaling in different cellular contexts (Ahmad et al 2015;Ma and Hottiger 2016;Mohan et al 1998;Nelson et al 2013). For example, there is evidence of bidirectional communication between Wnt and NF-ĸB signaling, and we have previously shown that Wnt-signaling promotes formation of proliferating MGPCs in the chick retina (Gallina et al, 2015), which is consistent with findings in mouse and fish retinas (Meyers et al, 2012;Meyers et al, 2012;Osakada et al, 2007;Yao et al, 2016;Yao et al, 2018). It has been shown that over-expression of β-catenin, a transcriptional effector of Wnt, suppresses NF-ĸB activity and expression of NF-ĸB target genes (reviewed by (Ma and Hottiger, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…There is evidence for cross-talk between many of these pathways with NF-ĸB signaling in different cellular contexts (Ahmad et al 2015;Ma and Hottiger 2016;Mohan et al 1998;Nelson et al 2013). For example, there is evidence of bidirectional communication between Wnt and NF-ĸB signaling, and we have previously shown that Wnt-signaling promotes formation of proliferating MGPCs in the chick retina (Gallina et al, 2015), which is consistent with findings in mouse and fish retinas (Meyers et al, 2012;Meyers et al, 2012;Osakada et al, 2007;Yao et al, 2016;Yao et al, 2018). It has been shown that over-expression of β-catenin, a transcriptional effector of Wnt, suppresses NF-ĸB activity and expression of NF-ĸB target genes (reviewed by (Ma and Hottiger, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…However, the study presented here demonstrates that PNU-282987 was able to elicit a significant neurogenic response through Müller glia without triggering apoptosis, as indicated by the lack of caspase 3 activity. Interestingly, recent work in adult mice has shown that modulation of Wnt signaling can also induce cell cycle rentry in Müller glia (Yao et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, mammalian MG undergo reactive gliosis upon retinal injury and disease, but do not naturally regenerate lost cells (Fischer & Reh, 2003;Inman & Horner, 2007;Karl & Reh, 2010;Reichenbach & Bringmann, 2013). During the last decade, various evidence has indicated that a limited amount of MG-derived neuronal regeneration can be experimentally stimulated in rodents (Del Debbio et al, 2010;Giannelli, Demontis, Pertile, Rama, & Broccoli, 2011;Harada et al, 2011;Insua et al, 2008;Jayaram et al, 2014;Joly, Pernet, Samardzija, & Grimm, 2011;Karl et al, 2008;Lawrence et al, 2007;Ooto et al, 2004;Osakada et al, 2007;Pollak et al, 2013;Reyes-Aguirre et al, 2013;Takeda et al, 2008;Ueki et al, 2015;Wan et al, 2008;Wan, Zheng, Xiao, She, & Zhou, 2007;Wang et al, 2012;Yao et al, 2016;Zhao et al, 2014), and that the extent might depend on animal age (Close, Liu, Gumuscu, & Reh, 2006;L€ offler, et al, 2015;Ueki et al, 2012) and the mouse strain (Suga, Sadamoto, Fujii, Mandai, & Takahashi, 2014).…”
mentioning
confidence: 99%